EDUCATION ON MARRIAGE DISPENSATION AFTER AMENDMENT TO LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE IN THE BATAM RELIGIOUS COURTS - Aozora Ratu Pitaloka; Rahmi Ayunda (Universitas Internasional Batam, 2022)
The Batam Religious Court Class 1-A is a religious court of the first level which has the authority in certain civil cases for Muslims, one of which is the case for applying for a marriage dispensation. Dispensation is an exception for the prospective bride and groom who are underage to get married. Article 7 paragraph (1) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage limits the age of marriage, namely the prospective bride and groom must be 19 years old. However, the fact is that early marriage is a phenomenon that occurs in society. The Office of Religious Affairs (KUA) will reject marriage if the prospective bride and groom are not of the specified age, so the parents of the prospective bride and groom must apply for a marriage dispensation in order to get a court product in the form of a stipulation as a permit for a marriage to take place. The implementation method uses observation techniques, namely by obtaining data in the field, carried out by interviews and collecting library data. The results and outcomes achieved are participation and contribution in the work environment of the Batam Religious Court, knowing and understanding procedures related to the requirements for submitting a marriage dispensation application, being able to serve people who want to have litigation, as well as providing insightful knowledge to the community with the existence of educational posters related to the Marriage Dispensation.